DEVELOPMENT OF INDIGENOUS LABORATORY SCALE GAS ATOMIZER FOR PRODUCING METAL POWDERS - Khan, K. K.; Qasim, A. M.; Ahmed, P. (The Nucleus, 2010)
Gas atomization is one of the methods for production of clean metal powders at relatively moderate cost. A laboratory scale gas atomizer was designed and fabricated indigenously to produce metal powders with a batch capacity of 500g of copper (Cu). The design includes several features regarding fabrication and operation to provide optimum conditions for atomization. The inner diameter of atomizing chamber is 440 mm and its height is 1200 mm. The atomizing nozzle is of annular confined convergent type with an angle of 25o . Argon gas at desired pressure has been used for atomizing the metals to produce relatively clean powders. A provision has also been made to view the atomization process. The indigenous laboratory scale gas atomizer was used to produce tin (Sn) and copper (Cu) powders with different atomizing gas pressures ranging from 2 to 10 bar. The particle size of different powders produced ranges from 40 to 400 Âµm.